Molecular Detection of Sus scrofa DNA Using IGF2 Gene Primers as Proof of Concept for Sybr Green-based Qualitative Real-time PCR - Raden Rara Bhintarti Suryohastari; Muhammad Saltes Albiansyah; Rizky Intan Novianti; Siti Hajar Hijriyah (Al-Kauniyah: Jurnal Biologi, 2026)
Detection of porcine (Sus scrofa) DNA is essential for halal meat authentication and requires highly specific and reproducible molecular assays. This study evaluated insulin-like growth factor 2 (IGF2) gene primers as a proof of concept for qualitative detection using SYBR Green-based real-time PCR. The IGF2 locus was selected due to its interspecies sequence divergence and reported specificity to Sus scrofa. Qualitative analysis included Sus scrofa DNA, Bos taurus DNA as a non-target control, and a no-template control (NTC). Conventional PCR identified 58 °C as the optimal annealing temperature. In real-time PCR, Sus scrofa DNA was consistently detected with a mean cycle threshold (Ct) of 29.22 ± 0.11 and a low coefficient of variation (CV) of 0.38% across three technical replicates, indicating high intra-assay precision. Melting curve analysis yielded a single, well-defined peak with a melting temperature (Tm) of 80 °C, supporting the amplicon's specificity. These findings supported the development of feasible IGF2 primers for the qualitative detection of Sus scrofa DNA using real-time PCR with shorter amplicons, which served as a foundation for further validation of the qPCR assay.